Encyclopedia of Public Administration and Public Policy - Jack Rabin (Taylor & Francis Group, 2005)
This chapter discusses how the value of economic efficiency, which is typically associated with private business accounting and operations, is increasingly being used to measure private nonprofit accounting and operations financial performance. Since the mid-1990s, private nonprofit organizations under the Financial Standards Accounting Board (FASB) have begun to follow the full cost accrual and consolidation model that is associated with measuring economic efficiency. This change suggests that the public choice philosophy (business efficiency in government and nonprofits) has cast its shadow over the traditional progressive philosophy (social mission) that historically was the model of operations in private nonprofit organizations. Specifically, the use of full costing for every project, taking a hard look at projects that are not ‘‘breaking even,’’ obtaining more outputs for less input, and putting extra emphasis on ‘‘earned income’’ in the form of donations are now all associated with the new nonprofit environment. Whether the pendulum will swing back to having social mission instead of economic efficiency being the primary criteria by which private nonprofits are judged is a critical question given the importance of the work that nonprofits undertake. With issues like environmental degradation, poverty, and international unrest in the forefront of the news, more pressure is placed on private nonprofit organizations to address these issues. How should the increasingly important private nonprofit sector account, measure, and report success?